Identification of Eimeria spp. in domestic chickens raised in alternative poultry production systems in the State of São Paulo, Brazil - José Carlos Soares Júnior; Bruno Ferraz Itoyama; Bruna Matarucco Sampaio Beretta; Camila Michele de Souza Hossotani; Maria Santa Cardoso Silva; Giane Serafim da Silva; Alex Akira Nakamura; Flávia Lombardi Lopes; Marcelo Vasconcelos Meireles (Revista Brasileira de Parasitologia Veterinária, 2023)
Abstract The objective of this study was to identify Eimeria spp. in alternative poultry production systems (APPS) in the State of São Paulo, Brazil. Fecal samples (168) and DNA extracted from fecal samples obtained in APPS located in different Municipalities in the State of São Paulo (93) were examined by microscopy or genera-specific PCR (ITS-1 locus). Samples positive for Eimeria spp. were examined using Eimeria lata, Eimeria nagambie, and Eimeria zaria species-specific PCR protocols (ITS-2 locus) and another E. lata-specific PCR (candidate IMP1 genomic locus) followed by molecular cloning (E. lata and E. zaria ITS-2 amplicons) and genetic sequencing. All positive DNA samples were also submitted to genera-specific nested PCR (18S rRNA gene) followed by next-generation sequencing to identify Eimeria spp. Eimeria nagambie, E. zaria, and Eimeria sp. were identified by ITS2-targeted species-specific PCRs and genetic sequencing. Next-generation sequencing identified, in order of prevalence: E. nagambie; Eimeria acervulina; Eimeria mivati; Eimeria praecox; Eimeria brunetti; Eimeria mitis; Eimeria sp.; Eimeria maxima; E. zaria, and Eimeria necatrix/tenella. Our results confirmed, for the first time in Brazil, the identification of E. nagambie, E. zaria, and Eimeria spp. ITS-2 and 18S rRNA gene sequences not yet described in Brazil.